2015
DOI: 10.3390/jcm4040715
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress in the Diabetic Kidney, the Good, the Bad and the Ugly

Abstract: Diabetic kidney disease is the leading worldwide cause of end stage kidney disease and a growing public health challenge. The diabetic kidney is exposed to many environmental stressors and each cell type has developed intricate signaling systems designed to restore optimal cellular function. The unfolded protein response (UPR) is a homeostatic pathway that regulates endoplasmic reticulum (ER) membrane structure and secretory function. Studies suggest that the UPR is activated in the diabetic kidney to restore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 212 publications
(270 reference statements)
1
39
0
1
Order By: Relevance
“…During its early phase, the UPR either refolds the accumulated unfolded proteins or degrades them via the ubiquitin-proteasome pathway 54 . When the unfolded protein and cellular damage exceed a threshold and the chronic cell stress is not relieved, proapoptotic responses are initiated and cell death ultimately ensues 55, 56 . Although our studies were not designed to assess the role of ROS in promoting kidney injury, we found that 4-HNE, an indicator of lipid peroxidation and oxidative stress, was markedly upregulated in hypertensive kidneys of GK-AC rats compared to normotensive kidneys of the same diabetic rats or hypertensive kidneys of Wistar-AC rats after 8 weeks of AC.…”
Section: Discussionmentioning
confidence: 99%
“…During its early phase, the UPR either refolds the accumulated unfolded proteins or degrades them via the ubiquitin-proteasome pathway 54 . When the unfolded protein and cellular damage exceed a threshold and the chronic cell stress is not relieved, proapoptotic responses are initiated and cell death ultimately ensues 55, 56 . Although our studies were not designed to assess the role of ROS in promoting kidney injury, we found that 4-HNE, an indicator of lipid peroxidation and oxidative stress, was markedly upregulated in hypertensive kidneys of GK-AC rats compared to normotensive kidneys of the same diabetic rats or hypertensive kidneys of Wistar-AC rats after 8 weeks of AC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibiting EGFR activation may also serve as a therapeutic target for DN. In addition, Endoplasmic reticulum (ER) stress, with misfolded and/or unfolded proteins in ER membranes, has been shown to mediate DN development and progression [10]. The crosstalk between ER stress and ROS production is well established in cancer biology, in which increasing ROS induces ER stress to trigger cancer cell apoptosis [1113].…”
Section: Introductionmentioning
confidence: 99%
“…TUDCA) has been shown to improve symptoms of renal diseases. There are a number of comprehensive reviews covering ER stress and renal damage, and therefore, this will not be discussed here (Cunard, ; Taniguchi & Yoshida, ; Wang et al . ).…”
Section: Introductionmentioning
confidence: 99%